Impact of buyer-supplier TMT misalignment on environmental performance. Issue 11 (2nd November 2020) - Kumar, Anupam; Steven, Adams; Paraskevas, John-Patrick
Abstract : Purpose: This study investigates the relationship between buyer-supplier top management team (TMT) demographic misalignment (defined as differences in TMT composition based on background, age and gender) and environmental performance (EVP). Design/methodology/approach: The empirical setting is publicly held US manufacturing firms that are present in both the Kinder, Lydenberg and Domini's (KLD's) annual EVP ratings and Bloomberg's supply chain database. The study employs panel data regression methods on an unbalanced panel dataset of 7, 493 dyad-year observations comprising 427 unique firms. Findings: The research shows that misalignment in functional background and gender composition between TMTs have a negative outcome on both the buyer's and the suppliers' EVP. However, increasing presence of females across TMTs has a positive influence on EVP. Further, the research shows that misalignment based on age between the TMTs does not impact EVP in any significant way. On the contrary, increasing age across TMTs is a significant predictor of EVP. Originality/value: This study builds on existing works in TMT heterogeneity and adds context to the heightening belief in the positive linkage between heterogeneity and performance through extension to a boundary spanning interfirm context.